Comparación entre la simulación clínica y la educación convencional en sepsis. Revisión sistemática de la literatura (2024)
Simulation as a didactic tool in healthcare has grown in the last decade. It is used as an educational strategy from nursing to medicine, including the training of students, residents and specialists. Some studies have estimated medical error up to 83%, which seems to be related to difficulties in generating teamwork and/or lack of communication, which is why it is necessary to generate changes in the mental model of health personnel, facilitating adherence to the package of measures in patients with sepsis. The aim of this study was to determine the available evidence on the use of simulation compared to conventional education in sepsis to improve the adherence of medical students to the different packages included in the sepsis survival campaign and the impact of the training methods.